The Government as Shareholder and Principal-Principal Conflicts in the Brazilian Electric Power Industry - Murialdo Loch; Jaison Caetano Silva; Giovana Bueno; Rosilene Marcon (BBR: Brazilian Business Review)
Considering that principal-principal conflicts in companies under mixed public-private ownership are substantially different from the typical agency conflict model, this paper’s objective is to analyze principal-principal conflicts in mixed ownership companies in the Brazilian electric power industry. In order to expand understanding of the phenomenon which we are studying, we have integrated the assumptions that underlie agency theory and institutional theory, using a qualitative approach and collecting data during semi structured interviews with companies’ board members. Data was analyzed and interpreted as per Bardin (2006), with the aid of ATLAS®ti software. Our main findings suggest that while a government stake in a firm’s ownership structure can provide a useful channel for the government to seek support and resources, in counterpoint, it can also create distortions and uncertainties, and exacerbate principal-principal conflicts. The development of stronger institutions and corporate governance could bring about useful options for providing checks and balances and, in the final analysis, mitigate principal-principal conflict. The article contributes to the literature by providing additional elements that are not available in public reports. Analysis of the conflict between principal and principal, together with theoretical integration, seek to broaden the understanding of this theme.